Role of Pituitary Tumour Transforming Gene 1 in Medullary Thyroid Carcinoma - Maria Chiara Zatelli; Federico Tagliati; Vincenzo Amodio; Mattia Buratto; Mariarosa Pelizzo; Giancarlo Pansini; Marta Bondanelli; Maria Rosaria Ambrosio; Ettore C. degli Uberti (Analytical Cellular Pathology)
Background: Pituitary tumour transforming gene 1 (PTTG1) is over-expressed in a variety of endocrine-related tumours. We aimed at evaluating PTTG1 expression and function in human neoplastic parafollicular C-cells, represented by medullary thyroid carcinoma (MTC) and C-cell hyperplasia (CCH) samples and by the TT cell line.